Optimizing a conventional PCR protocol to detect viroids Avocado sunblotch viroid (ASBVd ) And Potato spindle tuber viroid ( PSTVd ) of Persea americana Mill - María Valderrama Valencia (2017)
The avocado (Persea americana Mill) is a plant food interest, the problem at the level of the crop are diseases that reduce both plant and post-harvest quality; among them are produced by the viroids, including Avocado you have to sunblotch viroid (ASBVd) and Potato spindle tuber viroid (PSTVd) who dramatically reduce the organoleptic properties of the fruit. During the production process of said culture is needed pathogen free seedlings necessitating early detection. Currently there are methods of detecting an estimated cost of 24 USD through the use of real-time PCR technique.In the search for methods cheaper and reliable detection it was carried out standardization of a conventional PCR protocol that allows reducing the cost of detecting viroid in avocado mother plants. To this was done using the technique of reverse transcriptase reverse coupled the polymerase chain reaction (RT-PCR) end time using the kit One-Step RT-PCR (Novagen) and Two-step (Promega), the the second gave the best result. Finally it was possible to amplify the bands that identify viroids using the PCR technique final time, thus reducing the cost of detection of approximately USD 12 per sample.